15.7k views
2 votes
How do I do this, I’m unsure how to go about it

How do I do this, I’m unsure how to go about it-example-1
User Meri
by
4.8k points

1 Answer

4 votes

Given:


\sqrt{(6)/(x)}\cdot\sqrt{(x^2)/(24)}

Simplify:


=\sqrt{(6)/(x)}\cdot(√(x^2))/(√(24))=\sqrt{(6)/(x)}\cdot(x)/(2√(6))

Apply the properties of fractions:


=\frac{\sqrt{(6)/(x)}x}{2√(6)}

Simplify:


=((√(6))/(√(x))x)/(2√(6))=(√(6)√(x))/(2√(6))

Eliminate common terms:


=(√(x))/(2)

Answer:


(√(x))/(2)

User Niuer
by
4.8k points